2012
DOI: 10.1242/jcs.103176
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of interactions of the physiological anti-hypertensive peptide catestatin with the neuronal nicotinic acetylcholine receptor

Abstract: SummaryCatestatin (CST), a chromogranin-A-derived peptide, is a potent endogenous inhibitor of the neuronal nicotinic acetylcholine receptor (nAChR). It exerts an anti-hypertensive effect by acting as a 'physiological brake' on transmitter release into the circulation. However, the mechanism of interaction of CST with nAChR is only partially understood. To unravel molecular interactions of the wild-type human CST (CST-WT) as well as its naturally occurring variants (CST-364S and CST-370L, which have GlyRSer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 58 publications
2
10
0
6
Order By: Relevance
“…The present findings suggest that its thymic production and/or release are under cholinergic control involving nAChR containing the α 3-subunit. On the other hand, catestatin is an inhibitor of α 3 β 4 nAChR [49], so that it might act in an autoinhibitory feedback in α 3-subunit-expressing terminally differentiated mTEC.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings suggest that its thymic production and/or release are under cholinergic control involving nAChR containing the α 3-subunit. On the other hand, catestatin is an inhibitor of α 3 β 4 nAChR [49], so that it might act in an autoinhibitory feedback in α 3-subunit-expressing terminally differentiated mTEC.…”
Section: Discussionmentioning
confidence: 99%
“…Germane to acetylcholine receptors involvement, alpha-3 nicotinic receptor [27], regulates CGA, a protein stored and co-released with catecholamines [28]. CGA potentiated the visceromotor response to the nociceptive action of capsaicin which modulates C-fiber activity [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…When applied to the interaction between a-conotoxins and AChBP, this new molecular modeling tool gave good results compared with experimental available data [120]. In another recent study, docking and MD simulations of an a3b4 nAChR homology model with calestatin, a known endogenous peptide inhibitor of nAChRs, showed that this peptide acts by occluding the pore in the extracellular vestibule region of the receptor [121].…”
Section: Extracellular Domain Of Nachrsmentioning
confidence: 91%